We're one big family - Abd Razak, Dzulkifli (2007)
TEN years after the Asian economic crisis, an independent panel of "eminent persons" for the Manilabased Asian Development Bank (ADB) in a recent report noted that by 2020,90 per cent of Asians will live in middleincome countries. The region will account for nearly 45 per cent of global domestic product and 35 per cent of the world trade (WSJ, May 4-6). The panel, however, was quick to point out: "This broadly favourable outlook is plausible if there are no unexpected major crisis in the world economy or political upheavals in the region." In the same breath, in a speech earlier this year, the ADB president observed: "The gap between rich and poor —both across the countries and within each country—is growing."